Natural killer cells: Innate immune system as a part of adaptive immunotherapy in hematological malignancies - Demel, Ivo; Koristek, Zdenek; Motais, Benjamin; Hajek, Roman; Jelinek, Tomas (American journal of hematology, 2022)
Natural killer (NK) cells are part of a phylogenetically old defense system, which is characterized by its strong cytolytic function against physiologically stressed cells such as tumor cells and virus-infected cells. Their use in the treatment of hematological malignancies may be more advantageous in several ways when compared with the already established T lymphocyte-based immunotherapy. Given the different mechanisms of action, allogeneic NK cell products can be produced in a non-personal based manner without the risk of the formidable graft-versus-host disease. Advanced manufacturing processes are capable of producing NK cells relatively easily in large and clinically sufficient numbers, useable without subsequent manipulations or after genetic modifications, which can solve the lack of specificity and improve clinical efficacy of NK cell products. This review summarizes the basic characteristics of NK cells and provides a quick overview of their sources. Results of clinical trials in hematological malignancies are presented, and strategies on how to improve the clinical outcome of NK cell therapy are discussed.
Keywords: hematologické nádory; buňky NK; Immunologic Factors; nádory; Killer Cells, Natural; Immunotherapy, Adoptive; imunologické faktory; Humans; imunoterapie adoptivní; lidé; imunoterapie; Hematologic Neoplasms; Immunotherapy; Neoplasms